The Effect of Park and Urban Environments on Coronary Artery Disease Patients: A Randomized Trial. (16th June 2015) - Grazuleviciene, Regina; Vencloviene, Jone; Kubilius, Raimondas; Grizas, Vytautas; Dedele, Audrius; Grazulevicius, Tomas; Ceponiene, Indre; Tamuleviciute-Prasciene, Egle; Nieuwenhuijsen, Mark J.; Jones, Marc; Gidlow, Christopher
Abstract : Aim . To test the hypothesis that walking in a park has a greater positive effect on coronary artery disease (CAD) patients' hemodynamic parameters than walking in an urban environment. Methods . Twenty stable CAD patients were randomized into two groups: 30-minute walk on 7 consecutive days in either a city park or busy urban street. Wilcoxon signed-rank test was employed to study short-term (30 min) and cumulative changes (following 7 consecutive days of exposure) in resting hemodynamic parameters in different environments. Results . There were no statistically significant differences in the baseline and peak exercise systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), exercise duration, or HR recovery in urban versus park exposure groups. Seven days of walking slightly improved all hemodynamic parameters in both groups. Compared to baseline, the city park group exhibited statistically significantly greater reductions in HR and DBP and increases in exercise duration and HR recovery. The SBP and DBP changes in the urban exposed group were lower than in the park exposed group. Conclusions . Walking in a park had a greater positive effect on CAD patients' cardiac function than walking in an urban environment, suggesting that rehabilitation through walking in green environments after coronary events should be encouraged.